2004
DOI: 10.1016/j.jtcvs.2003.09.055
|View full text |Cite
|
Sign up to set email alerts
|

The Impella Recover microaxial left ventricular assist device reduces mortality for postcardiotomy failure: a three-center experience

Abstract: The Impella Recover device provides 3 to 4 L/min flow. It improves survival in patients with low-output syndrome if the heart is able to pump 1 L/min or more above device flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(68 citation statements)
references
References 11 publications
2
62
0
4
Order By: Relevance
“…Improved survival has been observed in cases with residual cardiac function higher than 1 L/min [1]. An adequate mean arterial pressure and cardiac output in absence of a peak of systolic pressure may guarantee peripheral organ perfusion unless a severe arterial stenosis is present as occurred in the case reported.…”
Section: Commentsmentioning
confidence: 69%
See 2 more Smart Citations
“…Improved survival has been observed in cases with residual cardiac function higher than 1 L/min [1]. An adequate mean arterial pressure and cardiac output in absence of a peak of systolic pressure may guarantee peripheral organ perfusion unless a severe arterial stenosis is present as occurred in the case reported.…”
Section: Commentsmentioning
confidence: 69%
“…However cases of functional mitral stenosis secondary to pump placement have been reported [8]. Minimal blood damage during pumping and a light anticoagulation level required provide a low rate of hemorrhagic complications [1][2][3][4]. Fig.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Impella device was associated with a higher level of hemolysis and one case of lower-limb ischemia following explantation (6). Other documented complications include sensor failure, functional mitral stenosis and displacement/repositioning (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…On the whole, repositioning remains poorly examined. Siegenthaler et al (11), reviewing their experience with the Impella device, found that four of 24 patients (approximately 17%) required device repositioning. It is unknown from the published report whether this was echocardiographically guided.…”
Section: Discussionmentioning
confidence: 99%